A metabolic pathway assembled by enzyme selection may support herbivory of leaf-cutter ants on plant starch - Bacci, Maurício [UNESP]; Bueno, Odair Correa [UNESP]; Rodrigues, André [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Somera, Alexandre Favarin [UNESP]; Silva, Aline (Elsevier, 2013)
Mutualistic associations shape the evolution in different organism groups. The association between the leaf-cutter ant Atta sexdens and the basidiomycete fungus Leucoagaricus gongylophorus has enabled them to degrade starch from plant material generating glucose, which is a major food source for both mutualists. Starch degradation is promoted by enzymes contained in the fecal fluid that ants deposit on the fungus culture in cut leaves inside the nests. To understand the dynamics of starch degradation in ant nests, we purified and characterized starch degrading enzymes from the ant fecal fluid and from laboratory cultures of L. gongylophorus and found that the ants intestine positively selects fungal α-amylase and a maltase likely produced by the ants, as a negative selection is imposed to fungal maltase and ant α-amylases. Selected enzymes are more resistant to catabolic repression by glucose and proposed to structure a metabolic pathway in which the fungal α-amylase initiates starch catalysis to generate byproducts which are sequentially degraded by the maltase to produce glucose. The pathway is responsible for effective degradation of starch and proposed to represent a major evolutionary innovation enabling efficient starch assimilation from plant material by leaf-cutters. © 2013 Elsevier Ltd.
Keywords: Amylase; Attini; Maltase; Mutualism; ant; biodegradation; entomology; enzyme activity; evolutionary biology; fungus; glucose; herbivory; metabolism; mutualism; starch